Comparative study on the fire-extinguishing effectiveness of N2 and CO2 on coal flame combustion - Guo Zhiguo; Wu Bing (矿业科学学报, 2017)
In order to master thoroughly the different fire-extinguishing effects of N2 and CO2 on coal flame combustion, the self-developed experiment device of coal flame combustion was used to conduct the fire-extinguishing experiment on coal flame combustion under the condition of importing same flux N2 and CO2 gas fire-extinguishing agent for coal samples in Eight mine of Ping Dingshan coal mine, and the change laws of temperature of temperature field, index gas formation (O2, CO and CH4), heat release rate and flame image area obtained from the experimental stages of the coal flame combustion and smoldering extinguished were measured.The results show that:compared to the free combustion of coal, in coal flame combustion stage, flame out time, coal temperature rise rate, oxygen consumption, heat release rate as well as the speed of CO and CH4 concentration decline in coal combustion with CO2 much lower than that of coal combustion with N2; meanwhile, the flame image area exponentially decline in coal combustion with CO2, but the flame image area linearly decreases in coal combustion with N2.In the coal smoldering extinguishes stage, the coal temperature, the speed of CO and CH4 concentration decline in the coal combustion with CO2 much higher than that of coal combustion with N2, but the oxygen consumption and heat release rate are lower.It follows that CO2 has greater capacity of extinguishing coal combustion compared to N2.